Інноваційні інструменти в українській науковій комунікації - Назаровець, Марина Анатоліївна (Київський національний університет імені Тараса Шевченка, 2017)
Розвиток інформаційних технологій призвів до змін у процесах наукової комунікації та ролі бібліотечної підтримки дослідницьких процесів. Для вивчення інноваційної комунікаційної ситуації бібліотекарі з Університету Утрехту (Нідерланди) Ієронім Босман та Бьянка Крамер провели глобальне онлайн-опитування ―Innovations in Scholarly Communication‖. У нашому дослідженні подано аналіз відповідей на опитування 117 українських респондентів, зроблений з метою виявлення основних тенденцій використання представниками української науки новітніх інструментів для комунікації. Використовувались методи аналізу, синтезу, узагальнення та інтерпретації отриманих даних для їх подальшого порівняння із загальносвітовими даними. В результаті дослідження було з’ясовано, що зміни дослідницьких робочих процесів пов’язані із розвитком цифрових технологій в Україні, за винятком окремих відмінностей, подібні до загальносвітових. Дані, отримані в результаті дослідження, можуть використовуватись в якості емпіричного матеріалу для подальших досліджень бібліотечно-інформаційного веб-супроводу дослідницької діяльності українських вчених.

The development of information technologies has led to changes in the processes of scientific communication and role of library support of research processes. Librarians from the Utrecht University (the Netherlands) Jeroen Bosman and Bianca Kramer conducted a global online survey ―Innovations in Scholarly Communication‖ to study the situation. The main objective of this our study is to identify the main trends in the usage of modern communication tools by Ukrainian scientists with the help of analysis of responses of 117 Ukrainian respondents who took part in this online survey. The source of the study is the open data set ―Innovations in scholarly communication – data of the global 2015-2016 survey‖, available at the Zenodo Scientific Repository. The results of surveys by Ukrainian respondents were selected for study from the main array of the open data. The calculated percentage of the received answers and the obtained results were compared with the global ones. The study found that changes in research workflows in Ukraine related to the development of digital technologies are similar to the global ones, with the exception of some differences. The data obtained as a result of the survey can be used as an empirical material for further research of the library web-support of Ukrainian scientists’ research activities. But given the rapid changes in the scientific communication landscape associated with both the development of information technology and increasing number of their users and their digital literacy, the current state of usage of these technologies in scientific process requires additional research.
Innovative Instruments in Ukrainian Scientific Communication
Keywords: наукова комунікація; web 2.0; наука 2.0; комунікаційні інструменти; наука в Україні; scholarly communication; science 2.0; communication tools; science in Ukraine